Anticipating the Flood. Community-based cartography for disaster flood events in Argentina - Gatti, Ignacio Agustin (2019)
Anticipando la Crecida Project (Anticipating the Flood) is an interdisciplinary project which deals with flood risk management strategies associated with intense rain events and southeasterly wind « sudestadas » in socio-economical vulnerable urban areas in Argentina. The objective of the current study is to use local knowledge through participatory activities to strengthen the phase of risk awareness of an early warning system by using cartography as a work tool. For this purpose, eleven workshops with adults and children were held between 2014 and 2017 in Buenos Aires metropolitan area and the towns of San Antonio de Areco and Santa Lucía. By helping communities articulate and communicate spatial knowledge through workshops, enable the possibility to advocate for a change. That change result in a new direction on how the community and stakeholders can act towards a flood event. Analysing community-based maps of 85 adults, flood theoretical models can be evaluated and perhaps improved. Additionally, overall 287 students between 10 and 17 years old learned about cartography and interacted with poster maps during the workshops held in different schools